Convective boiling of R-134a on enhanced-tube bundles - Gorgy, Evraam; Eckels, Steven J. (My University, 2016)
The current paper presents the experimental investigation of the heat transfer performance and effect of tube pitch on highly enhanced surface tube bundles. The fluid–tube combination used was R-134a and the enhanced tube TBIIHP. Three pitch-to-diameter ratios were studied: 1.167, 1.33, and 1.5; all with a staggered triangle arrangement. Twenty enhanced tubes were used in each bundle; the tube outer diameter and length are 19.05 mm (3/4 inch) and 1 m (39.36 inch), respectively. Three input variables were investigated: heat flux (5–60 kW/m2), mass flux (15–55 kg/m2.s), and quality (10–70%). The test saturation temperature was 4.44 °C. A local method employing the EBHT technique was implemented in data reduction. All tube bundles showed strong dependency on heat flux. The smallest P/D bundle showed a considerably lower performance than the other two. When compared to the pool boiling performance, the smallest P/D bundle was lower while the other two showed a closer performance. The P/D 1.33 bundle outperforms P/D 1.167 bundle and provide quite similar performance to the P/D 1.5. When considering the refrigerant quantity, the P/D 1.5 bundle uses more refrigerant compared to the P/D 1.33; the latter proves to be the optimum. Finally, a new enhanced tube heat transfer coefficient bundle model was proposed based on the extensive data collected and the studied bundle phenomena.
Ébullition convective du R-134a sur des faisceaux de tubes améliorés
Citation: Gorgy, E., & Eckels, S. (2016). Convective boiling of R-134a on enhanced-tube bundles. International Journal of Refrigeration, 68, 145–160. https://doi.org/10.1016/j.ijrefrig.2016.04.010
Keywords: Bundle void fraction; Boiling heat transfer; Convective boiling; EBHT analysis; Enhanced tubes; Tube bundle prediction